The differences between the expression levels of axe-txe genes in chloramphenicol-sensitive and penicillin-resistant Enterococcus faecium isolates - Sri Indra Wahyuni Mohd Irmal,; Suresh Kumar Subbiah,; Vasantha Kumari Neela,; Niazlin Mohd Taib,; Azmiza Syawani Jasni,; Maha Abdullah,; Mohamad Khairil Radzali,; Rukman Awang Hamat, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Toxin-antitoxin (TA) systems are important regulatory modules in bacterial physiological functions. In this study, Axe-Txe TA system of 20 Enterococcus faecium clinical isolates was investigated by polymerase chain reaction (PCR) using self-designed primers. The functionality of this TA system in two E. faecium isolates was evaluated by analysing the expression level of axe-txe genes using real-time quantitative PCR (RT-qPCR) in penicillin-resistant and chloramphenicol-sensitive environments at different points of time. Colony-forming units (CFU) of the bacteria were also measured at a similar point of time. The selection of these two isolates for TA functionality study was determined based on the susceptibility patterns of the two isolates to penicillin, the chloramphenicol via Kirby-Baur, and broth microdilution methods, which were then interpreted based on CLSI guidelines. Axe-Txe TA system was detected in both chromosomes and plasmids (100%, each) in all 20 isolates, while the selected two E. faecium isolates were sensitive to chloramphenicol (MIC = 4 µg/mL) and resistant to penicillin (MIC = 256 µg/mL). Although higher axe-txe genes expression was also observed in a chloramphenicol-sensitive environment at half an hour of the incubation period compared to the penicillin-resistant environment, higher expression of the axe-txe genes was found in the penicillinresistant environment at 1 h incubation period compared to the chloramphenicol-sensitive environment. Nevertheless, E. faecium isolates in both environments exhibited higher expression of txe gene (toxin) at the 24 h incubation period. Provided that the functionality of TA systems of E. faecium isolates may vary in different antibiotic environments, various environmental conditions need to be considered in the role of TA systems as potential antimicrobial targets. Different expression of TA genes in different antibiotic environments and points of time may influence the discovery and development of drugs in the future.